2017
DOI: 10.1108/ijbm-08-2016-0105
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods empirical exploration of UK consumer perceptions of trust, risk and usefulness of mobile payments

Abstract: Purpose The purpose of this paper is to explore UK consumer perceptions of trust, risk and perceived usefulness of mobile payments through the use of sequential mixed methods. Design/methodology/approach A post-positivist philosophy is used with a social constructionist ontology with a questionnaire as the first survey instrument using an empirical sequential mixed methods approach. Summary quantitative analysis of the questionnaire data is undertaken followed by semi-structured interviews that produce quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 70 publications
2
58
0
3
Order By: Relevance
“…con rmed that in the case of online services, trust was affected by the perceived ease of use and directly affected the perceived usefulness [90]. The perceived trust, among other factors, was identi ed by Hampshire as a key predictor of the perceived usefulness of mobile payment systems [116]. In the adopted model, trust in service was understood as a construct having a more technological character, so the questions were focused on technological solutions offered by a courier service provider.…”
Section: Resultsmentioning
confidence: 99%
“…con rmed that in the case of online services, trust was affected by the perceived ease of use and directly affected the perceived usefulness [90]. The perceived trust, among other factors, was identi ed by Hampshire as a key predictor of the perceived usefulness of mobile payment systems [116]. In the adopted model, trust in service was understood as a construct having a more technological character, so the questions were focused on technological solutions offered by a courier service provider.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is important to identify the nature of the research problem/questions at the first phase. Six of the eight sample studies (Brav et al, 2005;Chithambo & Tauringana, 2017;Davila & Foster, 2007;Englund & Gerdin, 2015;Hampshire, 2017;Tauringana & Chithambo, 2016) indicated in Table 1 have not clearly emphasized the rationale of the selected mixed method. The lack of identification of the rationale for mixed method study has been identified as the second research gap of the mixed method studies conducted in the finance discipline.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if the researcher has quantitative leanings, he will give priority to the quantitative phase if not otherwise. For instance, Hampshire (2017), Tauringana and Chithambo (2016), Davila and Foster (2007), Graham et al (2005), and Brav, Graham, Harvey, and Michaely (2005) conducted their finance-based studies assigning priority to the quantitative phase. We on the other hand argue that if there are no indicators to measure a concept or phenomenon, the qualitative design (e.g., in-depth interviews) takes priority followed by the developed indicators with a quantitative design (e.g., survey).…”
Section: The Rationale For a Triangulation/mixed Methods Inquirymentioning
confidence: 99%
See 2 more Smart Citations